2013
DOI: 10.1128/jb.00960-13
|View full text |Cite
|
Sign up to set email alerts
|

SMU.746-SMU.747, a Putative Membrane Permease Complex, Is Involved in Aciduricity, Acidogenesis, and Biofilm Formation in Streptococcus mutans

Abstract: Dental caries induced by Streptococcus mutans is one of the most prevalent chronic infectious diseases worldwide. The pathogenicity of S. mutans relies on the bacterium's ability to colonize tooth surfaces and survive a strongly acidic environment. We performed an ISS1 transposon mutagenesis to screen for acid-sensitive mutants of S. mutans and identified an SMU.746-SMU.747 gene cluster that is needed for aciduricity. SMU.746 and SMU.747 appear to be organized in an operon and encode a putative membrane-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Similarly, enhanced EPS production was noticed in S. mutans biofilm upon lmrB inactivation. The observed enhanced biofilm formation phenotypes of lmrB mutant cannot be caused by polar effect of mutations based on the observation that lmrB was a separate transcription unit ( Krol et al, 2014 ), which was in consistent with the notion that MFS members function as single-component pumps in Gram-positive bacteria ( Li and Nikaido, 2004 ). Therefore, it is intriguing how lmrB deletion affected the EPS production?…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, enhanced EPS production was noticed in S. mutans biofilm upon lmrB inactivation. The observed enhanced biofilm formation phenotypes of lmrB mutant cannot be caused by polar effect of mutations based on the observation that lmrB was a separate transcription unit ( Krol et al, 2014 ), which was in consistent with the notion that MFS members function as single-component pumps in Gram-positive bacteria ( Li and Nikaido, 2004 ). Therefore, it is intriguing how lmrB deletion affected the EPS production?…”
Section: Discussionsupporting
confidence: 84%
“…Transcription of ilvE is modulated by the global regulators CcpA and CodY (Santiago et al ., ). A recent study also indicated that the putative amino acid transporter encoded by SMU.745/SMU.746 was important for growth of S. mutans in acidified media, further indicating a role for amino acid metabolism in acid tolerance (Krol et al ., ).…”
Section: Maintenance Of An Alkaline Cytoplasmmentioning
confidence: 97%
“…mutans , a transposon screen found that the homologs SMU.746 ( scfA ) and SMU.747 ( scfB ) were important for the acid stress response and biofilm formation [ 51 ]. Although the authors hypothesized that the genes encoded for an amino acid permease, that was not demonstrated [ 51 ]. In B .…”
Section: Resultsmentioning
confidence: 99%